2022
DOI: 10.1002/jcop.22898
|View full text |Cite
|
Sign up to set email alerts
|

The impact of school climate in social‐normative expectations in low and high SES schools

Abstract: This study examined the associations among race/ethnicity, school climate, and social‐normative expectations (expectations about peers' future achievement) in high and low socioeconomic status (SES) schools, with a particular focus on school climate as a process that might influence social‐normative expectations. Results showed that more positive perceptions of school climate were significantly associated with higher levels of social‐normative expectations in both low and high SES settings. Additionally, ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…In addition, the findings of this research contribute to school institutions and public policies, as they contribute to decision-making processes and allow for evaluation and consequent intervention to improve school climate [14,22,69]. This allows multidisciplinary teams to work with the educational community to achieve social, emotional and academic benefits.…”
Section: Contributions For Practicementioning
confidence: 84%
See 1 more Smart Citation
“…In addition, the findings of this research contribute to school institutions and public policies, as they contribute to decision-making processes and allow for evaluation and consequent intervention to improve school climate [14,22,69]. This allows multidisciplinary teams to work with the educational community to achieve social, emotional and academic benefits.…”
Section: Contributions For Practicementioning
confidence: 84%
“…School climate is positively related to academic success [4,5,[19][20][21], academic achievement and student motivation [21]. It is highlighted that positive perceptions of school climate were significantly associated with high levels of socionormative expectations, that is, with students' high expectations about the future academic performance of their peers, which occurs in diverse socioeconomic environments [22]. In addition, an adequate school climate promotes learning for all students, especially those who may present some difficulty, such as hyperactivity/inattention [16].…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence (13)(14)(15)(16) suggests that improvements in the climate of a school can disrupt the negative link between low SES and poor academic achievement in various contexts, rendering it a key factor in promoting equal educational opportunities, which should be understood as a duty of all school community members, not only students, in order to promote high socio-normative expectations in schools. A recent study conducted with Chilean students indicated that a positive classroom climate compensates for the negative effects of low SES on SIMCE scores, i.e., maths tests (17).…”
Section: School Climatementioning
confidence: 99%
“…Finally, there is evidence to suggest that social-normative expectations, or the expectations one has for the achievements of one’s peers, can have an impact on the learning environment ( Bell et al, 2019 ; Vaid et al, 2023 ). Peer norms have been found to be an important factor in shaping students’ academic behaviors ( Dijkstra and Gest, 2015 ; Gremmen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Positive educational expectations are not only critical for promoting achievement, but these expectations may also be a protective asset for vulnerable, at-risk youth ( Herrenkohl et al, 2012 ; Gerard and Booth, 2015 ; Stoddard and Pierce, 2015 ; Brumley et al, 2017 ). While self-expectations are valuable to understand, social-normative expectations may assess a similar construct while reducing potential biases (self-serving bias theory; Miller and Ross, 1975 ; Shepperd et al, 2008 ) and provoke students to also think about potential environmental support and barriers ( Vaid et al, 2023 ). In fact, Sommerfeld (2016) found that social-normative expectations explained educational outcomes above and beyond accounting for self- and parental-expectations.…”
Section: Introductionmentioning
confidence: 99%